Métricas de Hausdorff induzidas em espaços homogêneos - Djeison Benetti (2016)
In this work we present Hausdorff metrics induced in quotient spaces. These metrics are determined by a left action of a group G in a connected metric space M, and provided in terms of Hausdorff distance among sets gX, g ∈ G, where X ⊂ M is a compact set previously fixed.